Mechanosynthesis, characterization, and adsorptive properties of Mg–Al-LDH and Zn–Al-LDH for olive mill wastewater treatment - Hosni, Khaled; Mahmoudi, Khaled; Haraketi, Manel; Jellali, Salah; Srasra, Ezzeddine (Comptes Rendus. Chimie)
Industrial olive oil production is of fundamental economic importance for many Mediterranean countries. However, this industry generates huge amounts of toxic olive mill wastewater (OMW), which could represent a serious threat to human health and environmental biodiversity. In the current study, calcined layered double hydroxides (LDHs) were synthesized through a mechanochemical process involving the manual grinding of magnesium or zinc- and aluminum-nitrate salts in an agate mortar, followed or not by a peptization process. The experimental results showed that non-peptized LDHs have a layered structure with relatively low crystallinity. However, the peptization process resulted in LDHs with regular particles exhibiting high crystallinity and thermal stability. These LDHs achieved a significant improvement in the quality of OMW. Indeed, after 44 h of contact time, the removed amounts of chemical oxygen demand (COD) and biological oxygen demand (BOD) were assessed at approximately 300 and 100 mg${· }$g$^{-1}$, respectively. Moreover, the discoloration rate of this effluent was more than 90%. Overall, the results demonstrate the convenience of the mechanosynthesis of hydrotalcite and the high efficiency of OMW treatment, which is promising for the potential applications of calcined LDH in environmental clean-up and remediation of contaminated water.